Hemodynamic Effects of Intravenous, High‐Dose Lipid Emulsion With and Without Metoprolol Infusion in Healthy Volunteers: A Randomized Clinical Trial. Issue 4 (26th December 2018) - Petersen, Kasper Meidahl; Bøgevig, Søren; Petersen, Tonny Studsgaard; Jensen, Thomas Bo; Dalhoff, Kim Peder; Henriksen, Trine; Poulsen, Henrik Enghusen; Christensen, Mikkel Bring
Abstract : In a double‐blinded, randomized, crossover trial, we investigated the hemodynamic effects of high‐dose intravenous lipid emulsion (ILE) with/without metoprolol. Ten healthy volunteers each completed 4 trial days (placebo + ILE; metoprolol + placebo; metoprolol + ILE; placebo + placebo) in random order. Metoprolol was administered as an initial bolus (10 mg), followed by an infusion (50 mg) from 5 to 30 minutes. ILE was administered as a bolus at 12.5 minutes (2.5 mL/kg), followed by a 15‐minute infusion (0.25 mL/kg per minute). On metoprolol + ILE days (compared with metoprolol + placebo) after 120 minutes, mean heart rates were significantly higher (difference, 5.5 beats per minute (bpm); 95% confidence interval (CI), 3.0–8.1 bpm; P  < 0.001), and average relative cardiac output was higher (difference, 10 percentage points; 95% CI, 5–15 percentage points; P  < 0.001). The hemodynamic effect of ILE developed gradually. ILE had no effect on plasma metoprolol or major adverse events. In conclusion, high‐dose ILE has relatively marginal and delayed hemodynamic effects that may have limited clinical relevance in the short‐term clinical toxicological setting.